Extensive and intensive margins of labour supply: Working hours in the US, UK and France - Richard Blundell; Antoine Bozio; Guy Laroque (Institute for the Study of Labor (IZA), 2011)
This paper documents the key stylised facts underlying the evolution of labour supply at the extensive and intensive margins in the last forty years in three countries: United-States, United-Kingdom and France. We develop a statistical decomposition that provides bounds on changes at the extensive and intensive margins. This decomposition is also shown to be coherent with the analysis of labour supply elasticities at these margins. We use detailed representative micro-datasets to examine the relative importance of the extensive and intensive margins in explaining the overall changes in total hours worked.
urn:nbn:de:101:1-201111029379
Keywords: J21; J22; 330; labor supply; employment; hours of work; Arbeitsangebot; Arbeitszeit; USA; Großbritannien; Frankreich